EVALUATION IMPLEMENTATION OF REVOLVING FUND PROGRAM SAMISAKE IN BENGKULU - Jatmiko Yogopriyatno (Perkumpulan Dosen Muda (PDM) Bengkulu, 2020)
There are two studies in this research; achievement analysis implementation, and improvement of the future program. This study uses descriptive qualitative method, the process of extracting data carried out by the method on a number of key informant interviews and documentation of data in the field. Analysis of data using analytical subprocesses and practices: (1) reduction of data and identification of patterns and (2) conclusion and present their conclusions. Based on the survey results revealed that First: the dimensions of Program Implementation identified that (a) the program has met the criteria for program correctness. (b) Output in the form of technical assistance programs and the number of beneficiaries as many as 9294 people with absorption budget of Rp 13,649,000,000.00. (c) Short-term outcome of labor to produce as much as 11.587, 8.322 and generate as much business units. (d) There was a discrepancy implementation of the initial design of the program. (e) Barriers to implementation of the program in the form of readiness resources, regulatory support, policy environment, and disobedience bureaucrats executor. Second; On-dimensional improvement program known that: (a) mathematically program has shown optimal performance with the percentage of short-term outcome by 23%. (b) There are three program areas that are the focus in the modification, namely; repair mechanism of revolving funds, enhanced dimensional mentoring programs, and compliance executive staff in terms of both quality and quantity of personnel. (c) The development of the modification program in the stage of formulation of the draft regulations are being discussed by the government.